A New Theoretical Study of Quantum Atomic Energy Spectra for Lowest Excited States of Central (PIHOIQ) Potential in Noncommutative Spaces and Phases Symmetries at Plan’s and Nanoscales - Abdelmadjid Maireche (Журнал нано- та електронної фізики)
In this research paper, we consider full phase-space noncommutativity in the Schrödinger equation (SE), we apply Boopp’s shift method and standard perturbation theory to the modified (SE) in order to obtain exactly new modified energy eigenvalues in noncommutative two dimensional real space-phase NC-2D: RSP for prolonged isotropic Harmonic oscillator plus inverse quadratic potential (PCIHOIQ potential) (central singular even-power potential (CSEP potential)) with novel two parts and , it is observed that the new energy dependent with new atomic quantum numbers, we have also constructed the corresponding modified anisotropic Hamiltonian operator.